Smart Agriculture: An Expert System for Tomato Plant Disease Diagnosis - Sheta, Alaa; Elashmawi, Walaa H.; Othman, Emad S. (ISBCom 2025, 2026)
Tomato plant diseases pose a significant threat to agricultural productivity, resulting in substantial economic losses. Early and accurate diagnosis is crucial for effective disease management. This paper describes the design and implementation of expert systems for tomato disease detection using the CLIPS (C Language Integrated Production System) platform. The tool is designed to help farmers and agronomists accurately identify diseases affecting tomato crops by simulating knowledge from professional experts. We carefully developed a set of rules to distinguish leaf blight symptoms from those of other tomato diseases and provided recommendations to minimize crop losses and maximize yields. The expert system was developed using a forward-chaining inference engine, and its performance was evaluated through a set of real-world test cases, demonstrating a high level of accuracy and consistency in decision-making. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2026.
Keywords: Blight; CLIPS; Consistency (knowledge bases); Expert System; Expert system; Inference engine; Knowledge Base; Plant Disease Diagnosis; Plant disease; Production (economics); Set (abstract data type); Tomato Diseases; dept.csc